Hubungan Status Merokok dengan Kejadian Ulkus Diabetikum pada Laki-Laki Penderita Diabetes Melitus - Shofia Aji Hidayatillah; Nugroho Heri; Mateus Sakundarno Adi (Jurnal Epidemiologi Kesehatan Komunitas, 2020)
Background: The incidence of diabetic ulcers in Indonesia is 12% and the risk of diabetic ulcers is 55.4% .10 Cases of diabetic ulcers and gangrene in Indonesia are the most known cases in hospitals. Mortality due to ulcers and gangrene ranges from 17-23%, while the amputation rate starts at 15-30%. Diabetic ulcers are the most common complication in people with Diabetes Mellitus (DM). The purpose of this study is to study the relationship of smoking with the incidence of diabetic ulcers in men with DM. The study design in this study is case control.Methods: This research was conducted in the outpatient and inpatient installation of RSUD dr. Loekmono Hadi Kudus Regency and RSI Sunan Kudus on August - September 2019. The population in this study were men with DM who received 25−80 years who had a health examination at dr. Loekmono Hadi Kudus Regency and RSI Sunan Kudus. A total of 35 cases and 35 controls were selected using consecutive sampling. Data were analyzed with chi square.Result: The results showed a significant relationship between smoking and the incidence of diabetic ulcers in men with DM (p = 0.030; 95% CI = 1,235-8,997) and physical activity (p = 0.015; 95% CI = 1,401-10,590).Conclusion: In this study, smoking and physical activity are related with the incidence of diabetic ulcers in men who are diabetic patients.